The importance of new forms of capital in nonprofit organizations: A case study of the Fafe delegation of the Portuguese Red Cross. Issue 7 (10th July 2017) - Mourão, Paulo; Pereira, Teresa; Moreira, Maria Cristina
Abstract : Purpose: The purpose of this paper is to understand the extent to which new forms of capital are noticed by different members of nonprofit organizations (directors, employees, and volunteers) and valued as a factor of organizational capacity. Design/methodology/approach: Using survey research methodology, the authors studied a nonprofit institution – a delegation of the Portuguese Red Cross located in Fafe, a city in northern Portugal, by giving a questionnaire to all its members. Findings: The respondents revealed that the existence of other forms of capital (in addition to financial capital) is recognized and valued and that human capital as a whole is particularly relevant to the fulfillment of the Fafe Delegation of Portuguese Red Cross' mission. Originality/value: This is the first study on the perceptions of human capital, social capital and financial capital in a Portuguese nonprofit organization.